Strategi Campaign Personalization Dalam Keberhasilan Pecah Telur PKB Pada Pemilu DPR-RI 2024 Di Daerah Pemilihan Jawa Barat - Vaza Sabila Ananda Rizqy; Wardani, Sri Budi Eko (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the winning strategy of the National Awakening Party (PKB) in gaining legislative seats in non-basic electoral districts (dapil) in the 2024 Election. The main focus of this study is the phenomenon of